(untitled) (MATEMATIKA, 2013)
A basal metabolic rate(BMR) that is too low is an indicator of a poor physical condition, and could be one of the reasons for overweight. Measuring BMR though, is a time-consuming exercise, and there has long been interest in developing statistical models to predict BMR from demographic and anthropometric measurements. Poh et al. [1] developed ordinary linear regression models on a cohort of 139 Malaysian children measured three years bi-annually. However, since each child contributed six times to the total data set, these models ignore the correlated nature of the data. We re-analyzed these data using correlated linear models. We show that our approach taking correlation into account is important to establish important covariates, but does not improve prediction. Keywords: Basal metabolic rate; correlated data linear model; linear mixed model 2010 Mathematics Subject Classification: 62P10